TRANSFORMATIONS OF THE INSTITUTION OF BLOOD FEUD AMONG THE PEOPLES OF THE CENTRAL CAUCASUS IN THE LATE 18TH – FIRST HALF OF THE 19TH CENTURY: FACTORS, MECHANISMS AND CASES - A. S. MIRZOEV (Кавказология, 2020)
The article, on the basis of archival documents, examines the features of the customary law of Kabardians in cases related to murder and blood feud, the system of compositions and its norms depending on the social status of the parties to the conflict, the institution of baramta, the impact of the Russian administrative control established in the region on the customary law implementation in the social practices of the peoples of the North Caucasus, its transformation, the distinctive features of the social psychology of representatives of the aristocratic estates, their ideas about class honor and ways of maintaining it. Despite the large number of studies devoted to customary law and traditional social institutions of the peoples of the North Caucasus, including the Kabardians, this topic cannot be considered comprehensively studied. Since 1822, in Kabarda, cases of "blood feud" were officially removed from the jurisdiction of traditional mediation courts and transferred to military courts for consideration in accordance with Russian law. In fact, the colonial administration did not act according to the "letter" of the law, but in accordance with the political situation and taking into account local customs. An analysis of the documents showed that in the 1840s, marked by the activation and success of the peoples of the Western and Eastern Caucasus in the anti-colonial war, the leadership of the Center of the Caucasian Line, which administratively included Kabardians and Karachais, pursued a flexible and rational policy in the judicial and administrative sphere. This policy facilitated the shift from the practice of blood revenge to the use of more compromise forms of resolution of conflicts caused by bloodshed.